Improvement of sensitization and intergranular corrosion of AISI type 304L stainless steel through thermo-mechanical treatment. (1st April 2023) - Shit, Gopinath; Mariappan, K.; Ningshen, S.
Abstract: In this study, solution annealed AISI type 304 L stainless steel (SS) was thermo-mechanically processed (TMP) by introducing different cold-rolled 20 and 40 percentages, followed by annealing at 900 °C and water quenching. Sensitization was carried out by heat treatment for 24 h at 675 °C. The degree of sensitization (DOS) was measured by the electrochemical double loop potentiokinetic reactivation (DL-EPR) technique, indicating high DOS (12.5%) for the as-received specimen. The grain boundary engineering (GBE) by TMP treatment substantially lowered the DOS (7.1%) and resistance against intergranular corrosion (IGC) in a boiling nitric acid medium. Graphical Abstract: Variation of degree of sensitization (DOS) and intergranular corrosion (IGC) with the grain size follow a 'Hall-Petch' type relationship. ga1 Highlights: All thermo-mechanical treated specimens demonstrated a higher value of Σ3. Thermo-mechanical treated specimens show improved DOS and IGC resistance. Both the DOS and IGC follow the 'Hall-Petch' relationship with grain size.